Membrane contacts with the endoplasmic reticulum modulate plastid morphology and behaviour - Mathur, Jaideep; Kunjumon, Thomas Kadanthottu; Mammone, Alena; Mathur, Neeta (Frontiers in Plant Science, 2023)
Plastid behaviour often occurs in tandem with endoplasmic reticulum (ER) dynamics. In order to understand the underlying basis for such linked behaviour we have used time-lapse imaging based analysis of plastid movement and pleomorphy, including the extension and retraction of stromules. Stable transgenic plants that simultaneously express fluorescent fusion proteins targeted to the plastid stroma, and the ER along with BnCLIP1-eGFP, an independent plastid envelope localized membrane contact site (MCS) marker were utilized. Our experiments strongly suggest that transient MCS formed between the plastid envelope and the ER are responsible for their concomitant behaviour.